2022
DOI: 10.3233/jad-220493
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Diesel Exhaust Particles

Abstract: Background: Air pollution particulate matter (PM) is strongly associated with risks of accelerated cognitive decline, dementia and Alzheimer’s disease. Ambient PM batches have variable neurotoxicity by collection site and season, which limits replicability of findings within and between research groups for analysis of mechanisms and interventions. Diesel exhaust particles (DEP) offer a replicable model that we define in further detail. Objective: Define dose- and time course neurotoxic responses of mice to DEP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This finding is consistent with the observations made by Alvarez et al, who reported that PM2.5 exposure impairs cognitive development in children [ 29 ]. On the contrary, previous studies have shown that exposure to DEPs in adulthood can have molecular and/or behavioral effects on the nervous system [ 30 , 31 ]. The discrepancies observed among these different studies may be attributed to variations in exposure components, timing, and dosage.…”
Section: Discussionmentioning
confidence: 97%
“…This finding is consistent with the observations made by Alvarez et al, who reported that PM2.5 exposure impairs cognitive development in children [ 29 ]. On the contrary, previous studies have shown that exposure to DEPs in adulthood can have molecular and/or behavioral effects on the nervous system [ 30 , 31 ]. The discrepancies observed among these different studies may be attributed to variations in exposure components, timing, and dosage.…”
Section: Discussionmentioning
confidence: 97%
“…Another limitation is that nPM lacks the polycyclic aromatic hydrocarbons (PAHs) in total ambient air pollution [ 69 ]. Future studies of PD and air pollution could consider using model particles, such as diesel exhaust particles (DEP) from the National Institute of Science and Technology (SRM 2975), which contain PAHs and can reliably induce neurotoxic responses as those caused by active nPM batches [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the primary focus of many studies has been on identifying biomarkers derived from EVs for differential diagnosis, there is a dire need to assess other metrics. These include prognostic insights, tracking disease progression, monitoring treatment responses, screening for risk, stratifying participants in clinical trials, interpreting drugs pharmacokinetics and pharmacodynamics and identifying responses to environmental toxins [232][233][234][235].…”
Section: Extending the Approach Beyond The Differential Diagnosismentioning
confidence: 99%